2008
DOI: 10.1002/chem.200701750
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Homolysis of a Nitrosylchromium Complex

Abstract: Metal(III)-polypyridine complexes [M(NN)(3)](3+) (M = Ru or Fe; NN = bipyridine (bpy), phenanthroline (phen), or 4,7-dimethylphenanthroline (Me(2)-phen)) oxidize the nitrosylpentaaquachromium(III) ion, [Cr(aq)NO](2+), with an overall 4:1 stoichiometry, 4 [Ru(bpy)(3)](3+) + [Cr(aq)NO](2+) + 2 H(2)O --> 4 [Ru(bpy)(3)](2+) + [Cr(aq)](3+) + NO(3)(-) + 4 H(+). The kinetics follow a mixed second-order rate law, -d[[M(NN)(3)](3+)]/dt = nk[[M(NN)(3)](3+)][[Cr(aq)NO](2+)], in which k represents the rate constant for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 48 publications
4
13
0
Order By: Relevance
“…The reactivity of nitric oxide (NO) remains a fundamentally important area of research. This is due in part to the extensive roles of NO in biology and in the environment. Nitric oxide is an integral part of immune response, vasodilatation, and platelet aggregation, ,, and compounds that release NO have been sought for their potential use as therapeutics. Several organic reagents, including alkyl nitrates (glyceryl trinitrate), alkyl nitrites (iso-amyl nitrite), and NONOates have been utilized as NO-releasing compounds. , Metal nitrosyl complexes have also been used as NO delivery agents, the classic example being sodium nitroprusside (Na 2 [FeNO(CN) 5 ], SNP). , Photodissociation, ,, reduction, and oxidation have all been employed to effect NO release from a metal nitrosyl complex. The latter two approaches, in particular, require a clear understanding of the redox chemistry of metal nitrosyl complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity of nitric oxide (NO) remains a fundamentally important area of research. This is due in part to the extensive roles of NO in biology and in the environment. Nitric oxide is an integral part of immune response, vasodilatation, and platelet aggregation, ,, and compounds that release NO have been sought for their potential use as therapeutics. Several organic reagents, including alkyl nitrates (glyceryl trinitrate), alkyl nitrites (iso-amyl nitrite), and NONOates have been utilized as NO-releasing compounds. , Metal nitrosyl complexes have also been used as NO delivery agents, the classic example being sodium nitroprusside (Na 2 [FeNO(CN) 5 ], SNP). , Photodissociation, ,, reduction, and oxidation have all been employed to effect NO release from a metal nitrosyl complex. The latter two approaches, in particular, require a clear understanding of the redox chemistry of metal nitrosyl complexes.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few well-defined examples of NO dissociation upon oxidation of a metal nitrosyl complex. For instance, Bakac and co-workers reported that the one-electron (1e – ) oxidation of [CrNO(H 2 O) 5 ] 2+ or [L 1 (H 2 O)CrNO] 2+ (L 1 = 1,4,8,11-tetraazacyclotetradecane) resulted in rapid denitrosylation. The putative 1e – oxidation products ([CrNOL 5 ] 3+ ) were not detected, suggesting that denitrosylation occurred immediately upon electron transfer. Similarly, Ledgzins and co-workers investigated the reactivity of [CpCr(NO)X 2 ] − (X = Cl, Br, I, OTf) with a variety of oxidants .…”
Section: Introductionmentioning
confidence: 99%
“…The reverse of reaction sometimes provides a useful route to NO for chemical and medicinal purposes. The kinetics of this step are a sensitive function of the ligand system, solvent, pH, and the metal. , As one might expect, the oxidation state of the metal strongly influences the NO dissociation rates, so that the reduction or oxidation , of inert nitrosyl complexes may provide a mechanism for NO release. In view of the complex electronic structure of nitrosyl complexes, with three limiting (M n - • NO, M n +1 -NO − , and M n −1 -NO + ) and countless intermediate electronic states, the entire MNO moiety should be considered the site of electron transfer, as opposed to purely metal-centered or NO-centered processes.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier work, , we have examined the oxidation of nitrosylchromium complexes Cr(H 2 O) 5 NO 2+ and L(H 2 O)CrNO 2+ (L = L 1 = 1,4,8,11-tetraazacyclotetradecane, and L 2 = meso -Me 6 -1,4,8,11-tetraazacyclotetradecane) with polypyridine complexes of iron(III) and ruthenium(III), M(NN) 3 3+ . Four equivalents of M(NN) 3 3+ were required for complete oxidation which yielded nitrate and Cr(III).…”
Section: Introductionmentioning
confidence: 99%
“…The rates of _NO dissociation vary with the M-NO bond strength, nature and oxidation state of the metal, ancillary ligands, etc. [1][2][3][4][5][6] Our past work in this area focused on thermally stable nitrosyl complexes of chromium 7 and rhodium, 8,9 and on mechanistic studies of their redox chemistry and photochemistry. 9,10 Among the rhodium complexes, the macrocyclic L 2 (H 2 O)Rh(NO) 2+ (L 2 ¼ meso-Me 6 -cyclam) was studied most extensively.…”
Section: Introductionmentioning
confidence: 99%